DESALINATION OF CHITOOLOGOSACCAHARIDES USING GEL FILTRATION AND ULTRAFILTRATION - Pujoyuwono Martosuyono; Asri Pratitis; Alexander Prasetya; Elisabeth Kartika Prabawati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Chitooligosaccharide (COS) , which is a derivative product from chitosan, has recently been used as a functional food because it has antimicrobial, antifungal, and antitumor properties. The salt content in chitooligosaccharide is one of the main problems in application as functional food or pharmaceutical medicine. The aim of this study was to remove salt from COS with two desalting techniques and determine the variation of COSs in the product. The desalting technique used were dialysis with 10kD Molecular Weight Cut Off (MWCO) and gel filtration chromatography HiPrep 26/10 desalting with G-25 Superfine Sephadex as stationary phase in the column. In order to detect the presence of COS, Thin Layer Chromatography (TLC) method was used, followed by Matrix-Assisted Laser Desorption-Ionization Time-of-Flight Mass Spectrometry (MALDI–TOF–MS) to detect low concentration of COS. Qualitative and quantitative analysis of salt presence were identified using silver nitrate and Volhard method respectively. Ash content was measured using gravimetric method. Results showed those dialysis and gel filtration chromatographies were successfully remove the most of the salt from COS with efficiency of desalting up to 100%. However, the best desalting technique was gel filtration chromatography HiPrep 26/10 which has more complete COS with various degrees of polymerization present in the result.